Distribution of Microplastic at Sediments in the Coast of Bungus Bay Padang West Sumatera Province - Islami, Muhammad Dinul; Elizal; Siregar, Yusni Ikhwan (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2020)
This research was carried out in July to August 2019. It aimed to learn the shape and the abundance of microplastics in the coastal area of Bungus Bay, West Sumatra Province. Survey method was applied and PVC pipe was used to collect sediment samples from three different stations with three sampling points on each station. The results showed that the abundance of microplastics were significantly different between stations, except at different sediment depths and tidal zones (it ranged from 191.11 - 301.11; 221.48 - 236.30; and 226.67 - 231.11 particles per kg of dry sediments consecutively). In addition, the microplastic with fiber type was higher than the two other types, such as films and fragments